Analysis on the Impact of Implementing Inter-band Carrier Aggregation (CA) on the 5G-NR Networks - Vanessa Agelliza; Solichah Larasati; Alfin Hikmaturokhman (Journal of Information Technology and Its Utilization, 2023)
Currently, cellular technology is advancing into the 5G era, which can support data speeds up to 10 Gbps on the uplink side and 20 Gbps on the downlink side. This study aims to plan a 5G NR network by implementing the inter-band carrier aggregation (CA) method. CA is one of the techniques used to achieve high data speeds and to combine two or more radio frequency bands. The primary cell uses band n40 at 2300 MHz with a 40 MHz bandwidth, while the secondary cell uses band n78 at 3500 MHz with a 100 MHz bandwidth. The area that we used for this network design is Agung Podomoro Land (APL) Tower Central Park area in West Jakarta. The propagation model used Urban Macro. Testing process is carried out by comparing the results between using CA and not using CA on the SSRSRP, SS-SINR, and data rate parameters. Simulation results show an average increase in each parameter after the inter-band carrier aggregation method is applied. The SS-RSRP parameter increased by 0.05% with a value of -82.02dBm, the SS-SINR parameter increased by 0.77% with a value of 15.71dB, and the data rate parameter significantly increased by 241.33% with a value of 803.66 Mbps. This proves that implementing the carrier aggregation method can improve the quality and capacity of the network, particularly the data rate, by maximizing the use of the bandwidth and resource block produced by the combination of component carriers.